Dynamics of charge-transfer excitons in a transition metal dichalcogenide heterostructure. Issue 15 (3rd April 2020) - Bian, Ang; He, Dawei; Hao, Shengcai; Fu, Yang; Zhang, Lu; He, Jiaqi; Wang, Yongsheng; Zhao, Hui
Abstract : Hot charge-transfer excitons are formed in a transition metal dichalcogenide trilayer heterostructure and diffuse during their cooling process. Abstract : Charge-transfer excitons are formed by photoexcited electrons and holes following charge transfer across a heterojunction. They are important quasiparticles for optoelectronic applications of semiconducting heterostructures. The newly developed two-dimensional heterostructures provide a new platform to study these excitons. We report spatially and temporally resolved transient absorption measurements on the dynamics of charge-transfer excitons in a MoS2 /WS2 /MoSe2 trilayer heterostructure. We observed a non-classical lateral diffusion process of charge-transfer excitons with a decreasing diffusion coefficient. This feature suggests that hot charge-transfer excitons with large kinetic energies are formed and their cooling process persists for about 100 ps. The long energy relaxation time of excitons in the trilayer compared to its monolayer components is attributed to the reduced carrier and phonon scattering due to the dielectric screening effect in the trilayer. Our results help develop an in-depth understanding of the dynamics of charge-transfer excitons in two-dimensional heterostructures.